Promoting Regional Industries Through Cross-Sectoral Collaborations: Regional System, Management, and the Management Body - Yuki Kawabata (IGI Global, 2023)
In the realm of regional industrial development, academic scholars often find themselves grappling with a complex dilemma; how to effectively navigate the complex landscape of cross-sectoral inter-organizational collaborations to catalyze the emergence of vibrant regional industries? Traditional management approaches, characterized by hierarchical structures, frequently fall short when confronted with the intricacies of these collaborations, which involve a multitude of autonomous and diversified entities. The need for a fresh perspective in this dynamic field has never been more evident. Promoting Regional Industries Through Cross-Sectoral Collaborations: Regional System, Management, and the Management Body is a transformative book offering an innovative and comprehensive solution to the challenges posed by regional industrial development. Its core mission is to provide a robust theoretical framework that addresses the critical question of how to manage and facilitate cross-sectoral collaborations effectively. The authors recognize that traditional hierarchical approaches are ill-suited to the task, and thus, they offer a groundbreaking alternative. The book guides scholars and practitioners on a journey that begins with the creation of a management approach designed to construct and operate a regional system conducive to self-organizing cross-sectoral collaborations. Drawing from rich literature and real-world case studies, it outlines a conceptual model that revolutionizes the approach to building and operating regional systems, ultimately redefining the management landscape. It delves into change management theory, offering practical insights and a comprehensive model to guide the management of self-organizing processes towards collaboration. Lastly, it explores the critical role of a management body in facilitating these collaborations and presents a practical roadmap for building and re-building this essential entity. For academic scholars seeking to revolutionize regional industrial development, this book provides the indispensable guidance needed to navigate the complex web of cross-sectoral collaborations effectively. It offers fresh perspectives, practical insights, and a roadmap to reshape the future of regional industries through innovation and collaboration.
Keywords: 650; Management and management techniques; Organizational theory and behaviour; Industrial management; Industries; Germany